Proceedings of the 2nd Annual Conference on Education and Social Science (ACCESS 2020) 2021
DOI: 10.2991/assehr.k.210525.125
|View full text |Cite
|
Sign up to set email alerts
|

Designing Blended Learning for Teaching English Grammar at Higher Education

Abstract: The mastery of English Grammar for Students of English Education Department (henceforth EED) has a multipurpose target, namely, to build their confidence in communication (both spoken and written), to prepare them to be English teachers, who need English grammar for teaching, and to meet their graduation requirement on the TOEFL score, one section of which demands a high level of grammar mastery. Thus, the series of English Grammar courses are expected to equip them with those competencies. However, based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…The greatest improvement has occurred among pupils with "unsatisfactory" grades; more than fifty per cent have improved their performance, and most agreed on the platforms' convenience and accessibility. This advantage is also supported by a study done by Sujana et al (2021), which stated the positive feedback from students from implementing Google Classroom, and a literature review from Yen and Mohamad (2020), which highlighted the use of e-learning to improve primary school ESL pupils on learning to spell. The implications of e-learning for ESL students in elementary school revealed that it can increase students' motivation and provide them with meaningful knowledge when learning to spell at their own pace.…”
Section: Introductionmentioning
confidence: 78%
“…The greatest improvement has occurred among pupils with "unsatisfactory" grades; more than fifty per cent have improved their performance, and most agreed on the platforms' convenience and accessibility. This advantage is also supported by a study done by Sujana et al (2021), which stated the positive feedback from students from implementing Google Classroom, and a literature review from Yen and Mohamad (2020), which highlighted the use of e-learning to improve primary school ESL pupils on learning to spell. The implications of e-learning for ESL students in elementary school revealed that it can increase students' motivation and provide them with meaningful knowledge when learning to spell at their own pace.…”
Section: Introductionmentioning
confidence: 78%
“…Dengan fasilitasi akun ini, peserta kegiatan dapat mempelajari materi-materi yang dibahas pada kegiatan offline dan belajar secara fleksibel sesuai dengan kebutuhan dan waktu yang dimiliki peserta. Hal ini sejalan dengan konsep pembelajaran bauran (Sujana, Arifuddin, Thohir, Udin, 2021).…”
Section: Tahap Presentasi Dan Diskusi Proposalunclassified